2016
DOI: 10.1007/s10964-016-0527-x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Callous–Unemotional Traits, Externalizing Problems, and Gender in Predicting Cognitive and Affective Morality Judgments in Adolescence

Abstract: Morality deficits have been linked to callousunemotional traits and externalizing problems in response to moral dilemmas, but these associations are still obscure in response to antisocial acts in adolescence. Limited evidence on young boys suggested that callous-unemotional traits and externalizing problems were associated with affective but not cognitive morality judgments. The present study investigated these associations in a community sample of 277 adolescents (M age = 15.35, 64 % females). Adolescents wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
(101 reference statements)
1
8
1
4
Order By: Relevance
“…In line with findings from adult research [e.g., ( 30 , 31 , 35 )] and a recent study with a youth community sample ( 45 ), we further found that adolescents with higher CU traits reported anticipating less guilt when imagining themselves performing everyday actions that cause harm to other people, and took longer to make these evaluations. This finding agrees with recent literature reporting emotional hypo-responsivity of children with high levels of CU traits, in particular to others' stress, manifested at behavioral, cognitive and neural levels (see 3, 49 for recent reviews).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with findings from adult research [e.g., ( 30 , 31 , 35 )] and a recent study with a youth community sample ( 45 ), we further found that adolescents with higher CU traits reported anticipating less guilt when imagining themselves performing everyday actions that cause harm to other people, and took longer to make these evaluations. This finding agrees with recent literature reporting emotional hypo-responsivity of children with high levels of CU traits, in particular to others' stress, manifested at behavioral, cognitive and neural levels (see 3, 49 for recent reviews).…”
Section: Discussionsupporting
confidence: 91%
“…This failure to distinguish between the two types of transgressions is thought to reflect diminished emotional resonance to the harm caused to the victim. More recently, Fragkaki et al ( 45 ) found that high levels of CU traits were associated with lower feelings of guilt when individuals were imagining themselves committing antisocial acts. Neuroimaging research suggests that the atypical moral behavior that children and youth with high CU traits display may stem from dysfunction in brain regions implicated in affective processing, namely the amygdala and the ventromedial prefrontal cortex [vmPFC; for a review see, ( 46 )].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of impaired executive functioning is most substantial for antisocial PD 155‐159 and CD 160,161 , followed by disinhibitory traits 162‐166 . Additionally, deficits in sustained attention, inhibitory control, and sluggish cognitive tempo are associated with ADHD 162,167‐172 .…”
Section: Validity Evidencementioning
confidence: 99%
“…Das Alter und das Geschlecht wurden als Kontrollvariablen mit aufgenommen. Die direkten Effekte des Geschlechts auf die aufgenommen Variablen entsprechen bisheriger Forschungsergebnisse zur Rolle des Geschlechts bei Callouss-unemotional Traits (Bleyer, Koglin & Petermann, 2017;Fragkaki, Cima & Meesters, 2016;Koglin & Petermann, 2012) zu Gunsten der Mädchen, sowie dem vorhandenen Geschlechterunterschied in der moralischen Identität (Hardy, Walker, Olsen, Woodbury & Hickman, 2014;Patrick, Rote, Gibbs & Basinger, 2019). Anders als der von Patrick et al (2019) herausgestellter Unterschied in der moralischen Identität zu Gunsten der Jungen zeigen sich die Unterschiede des Geschlechts in der moralischen Identität bei vorliegender und vergleich-barer Stichprobe jedoch zu Gunsten der Mädchen.…”
Section: Diskussionunclassified